A NEW CORRELATIONS FOR HEAT TRANSFER IN THE COOLING PROCESS OF AL2O3 –WATER NANOFLUIDS IN PIPE - Sudarmadji, Sudarmadji (Journal of Applied Engineering Science, 2015)
The experiment was done to investigate convection heat transfer in the cooling processes of Al2O3-water nanofluid with different concentrations of 0.15%, 0.25% and 0.5% by volume. The test section was a 1.25 m long with a 4.9 mm inner diameter pipe, was 1 mm thick and 38.5 mm outer of a counter flow double-pipe heat exchanger. The temperatures of the inlet side of the nanofluid of inner pipe and of outer pipe were constant, i.e, 40oC and 23oC, respectively. The results of this study indicated enhanced of coefficient convective heat transfer of the cooling process than of the heating process. The new equations of the Nusselt number obtained in the cooling process was at particle volume concentrations of 0.15%, 0.25% and 0.5%. The maximum ratio enhancement of the nanofluid heat transfer in the cooling process was 45.2% at a particle volume concentration of 0.25%, while for the heating process nanofluid heat transfer was same as that for pure water.